Self-healing properties of new surface treatments - Fedrizzi, L.; Fürbeth, Wolfram; Montemor, Fátima (Publications (European Federation of Corrosion) ;, 2011)
This publication was motivated by the highly successful workshop on self-healing coatings held on 12 September 2007 at the European Federation of Corrosion's annual EUROCORR conference in Freiburg. It includes sixteen contributions, some of which were selected from the proceedings of the workshop (often in extended form) together with a number of specially invited articles and reviews.